Development of Polyols from Vegetable Oils via Oxirane Ring Opening Technique for Polyurethane Applications - Venkatesh , Desappan; Jaisankar, Viswanathan (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
Vegetable oils are a promising source of raw materials for the production of high functionality polyols. These polyols are widely used in the manufacture of high-quality products such as polyurethanes and poly(ether urethanes). In this study, a series of bio-based triglyceride vegetable oils, including Sesamum indicum (sesame oil), Arachis hypogeae (peanut oil), Azadirachta indica (neem oil), Jatropha curcas (jatropha oil), and Madhuca longifolia (mahua oil), were used to prepare high molecular weight polyols. The effects of carboxyl to epoxy ratio on the ring opening of epoxy groups were investigated by using castor oil fatty diol. The resulting epoxidized oils and bio-polyols were characterized by Fourier Transform Spectroscopy (FT-IR), Proton Nuclear Resonance Spectroscopy (1H NMR), and Carbon Nuclear Resonance Spectroscopy (13C NMR). The molecular weight of the polyols was determined by Gel Permeation Chromatography (GPC), and the stability and decomposition of the polyols were characterized by thermogravimetric analysis (TGA). Rheometry was used to determine the viscosity of the polyols, and the flow rate of the polyols was derived from a power law model. The results showed that the bio-based polyols produced from vegetable oils exhibited excellent thermal stability, high molecular weight, and good rheological properties. This study provides valuable information for the development of bio-based polyols as an alternative to petroleum-based polyols. The use of vegetable oils in the synthesis of high functionality polyols could lead to a reduction in environmental pollution and provide a sustainable solution for the production of high-quality polyurethane materials.